Disability 2.0, student dis/connections: a study of student experiences of disability and social networks on campus in higher education - Lewthwaite, Sarah (2011)
For many young people, social networks are an essential part of their student experience. Using a Foucauldian perspective, this qualitative study explores the networked experiences of disabled students to examine how dis/ability difference is ascribed and negotiated within social networks. Data comprises 34 internet-enabled interviews with 18 participants from three English universities. Accessible field methods recognise participant preferences and circumstances. Data is analysed using discourse analysis, with an attention to context framed by activity theory.